Factors Influencing Access to Sexual Health Care Among Behaviorally Bisexual Men in Vientiane, Laos: A Qualitative Exploration. (November 2015) - Bowring, Anna L.; Pasomsouk, Nakhornphet; Higgs, Peter; Sychareun, Vanphanom; Hellard, Margaret; Power, Robert
In Laos, men who have sex with men (MSM) are disproportionately affected by HIV, and bisexual behavior among men is common. We conducted a qualitative study to explore access and influences on sexual health care seeking among bisexual men in Vientiane. In 2013, behaviorally bisexual men were recruited from bars, clubs and dormitories for 5 focus group discussions and 11 in-depth interviews. Participants (aged 18-35 years) commonly reported high-risk sexual behaviors, yet most had never been tested for HIV, and none reported testing for sexually transmitted infections. Common barriers to testing were low perception of risk, expectation of symptoms, fear of HIV, shyness, perceived stigma, confidentiality concerns, and waiting times. Many men were unaware of available services. Most clinics cannot provide comprehensive HIV and sexually transmitted infection services. Strategies are needed to generate demand for testing, improve the capacity of sexual health care providers, and promote available services among behaviorally bisexual men in Vientiane.